E-commerce, Inovasi, Pricing, dan Pendapatan UMKM di Masa Pandemi Covid-19 - Noansa Pramelia; Teguh Erawati (LPPM Institut Nasional Laa Roiba Bogor, 2022)
The purpose of this study was to determine the effect of e-commerce, innovation, and pricing on MSME income during the COVID-19 pandemic. The population of this research is MSME actors in Kulon Progo Regency. The method in this research is descriptive quantitative method. The sampling technique used was convenience sampling with a total of 101 respondents. Data was collected by distributing questionnaires in the form of a google form link. The data analysis technique used is multiple linear regression model. Based on the results of hypothesis testing in this study partially shows that the e-commerce variable has an effect on income. The innovation variable has an effect on income. The pricing variable has an effect on income. The results of the simultaneous test show that the calculated F value > F table is equal to (35.641 > 2.69) and a significance level (0.000 < 0.10) so it can be concluded that the variables of e-commerce, innovation, and pricing simultaneously have a positive and significant effect on revenue. SMEs. Judging from the results of the coefficient of determination R^2, 51% of MSME income is influenced by e-commerce, innovation, and pricing variables, while the remaining 49% is influenced by other factors not involved in this study..